Numerical Comparison of Natural Convection Heat Transfer in Air- and Water-Filled Enclosures - Fahim, Tanvir Ahmed; Rahman, Md. Mahbubur; Sharar, Inkiad Haque (SciEn Conference Series: Engineering, 2025)
This study investigates the natural convection heat transfer in a C-shaped enclosure filled with air and water through numerical simulation. The enclosure with varying aspect ratios (the ratio of outer length to inner length of the enclosure) is considered to examine the effects of both enclosure shape and fluid properties on heat transfer rate. The outer C-shaped boundary is set to a higher temperature compared to the inner one, while the connecting walls between the hot wall and cold rib are treated as adiabatic. The numerical analysis is conducted in ANSYS Fluent 20.2 assuming a 2-D problem setup at the Rayleigh number ranging from 104 to 106, capturing the behavior of both fluids under low to moderate buoyancy-driven flow conditions. Streamline and temperature contour visualizations in the result analysis reveal the formation of primary and secondary eddies, with central, large eddies dominating the enclosure and smaller eddies forming in the gap between the cold rib and hot wall. These secondary eddies promote mixing and enhance convective currents by disrupting the primary flow. This leads to increased circulation within the enclosure, thereby raising the heat transfer. Water-filled enclosures predominantly exhibit higher heat transfer than air-filled enclosures due to water’s superior thermal conductivity and heat capacity, which facilitate more intense convective eddy circulation. However, the eddy dynamics in air-filled enclosures can become especially favorable for transferring heat, even in comparison to water-filled counterparts This work underscores the role of enclosure shape and fluid properties in enhancing convective heat transfer, providing insights for optimizing thermal management in confined geometries.